La dramatización como estrategia de desarrollo emocional en los niños de 4 a 5 años de la Escuela de Educación Básica Gabriela Mistral Cantón Chillanes, provincia de Bolívar - Yuquilema Garcia, Blanca Norma (2019)
The objective of the research was to determine how the dramatization helps emotional development in children of 4 to 5 children of the Gabriela Mistral Basic Education School. The established methodology presents a mixed approach, that is, quali - quantitative, and is based on a descriptive scope. The study population was 26 children (14 boys and 12 girls) between the ages of 4 and 5, belonging to the school grade. In addition, a support guide was applied to strengthen the dramatization environment of emotional development. The t-student test statistic was used, and it was corroborated that the P value is less than 0.05. In this way, the hypothesis is verified, the dramatization IF influences the process of emotional development. The main results of the first application reflect that, 77% of students must improve their emotional skills, 15% need guidance and 8% is the group that knows how to handle these skills. On the other hand, the second application 88% learned to manage their skills and emotions, while the remaining 12%, will depend on the teacher and his direction to improve their emotional skills. In conclusion, it is determined that children show a marked creativity in the execution of dramatic activities, so that the successful inclination in the dramatic activitis in their classrooms generates expectations of intellectual development. Keywords: Dramatization, Emotional development, Psychomotor development, Theatrical pedagogy, Dramatic expression